FICTIONAL TIME AND SPACE IN THE PROSE OF SMALL ETHNIC GROUPS OF THE NORTH - Yulia G. Hazankovich (Studia Litterarum)
The essay bears on Mikhail Bakhtin’s idea of chronotope as “the gate” to “the sphere The essay bears on Mikhail Bakhtin’s idea of chronotope as “the gate” to “the sphere of meanings.” Without this methodological tool, it would be difficult to understand a national literature that is archetypal at its core. Fiction of the indigenous peoples of the North — Mansi, Khanty, Nenets, Evens, Evenks, Yukaghirs, Nivkhs, Chukchi, Nanais, etc. — is unique due to its specific chronotope that makes it strikingly different from the Russian literature that had nurtured the former. Systematic approach allows reveal the specificity of fictional time and space and the specific ways chronotope functions in the prosaic works of the North. The chronotopic aspect of the Northern fiction draws from the peculiar understanding of art and life and the national worldview of the Northern author. Most of the fictional characters are subject to the laws of their “own” space and measure everything with the measure of nature and race. Owing to this fact, the analysis of fictional time and space helps us understand the “obscure” characters that represent the national consciousness and trace hitherto unstudied chronotope formations of the Northern literature such as: chronotope of the nomad, chronotope of man and woman, chronotope of the road, chronotope of the fishery and hunting, chronotope of the elderly person, etc. The essay eventually demonstrates that mythology forms the basis of the literatures of small ethnic groups.